Проблема громадсько-політичної активності жінок у вітчизняній науковій думці - Олійник, Наталія (Видавництво Львівської політехніки, 2015)
Розглянуто стан наукової розробки проблеми громадсько-політичної активності жінок в Україні. Проаналізовано та систематизовано дослідження вітчизняних науковців для формування теоретико-методологічних засад створення цілісної картини участі жінок у політичному та громадському житті України, що може розглядатися як орієнтир для подальших наукових досліджень. The article is dedicated to the study of the women’s public and political activity in Ukraine. The author analyses the works of the Ukrainian scientists according to the periods (pre-Soviet, Soviet, modern), the scholars’ place of living (Ukrainian, diaspora) and the sphere of the investigated problems (the women’s financial position and education, the women’s liberation movement, the women’s political representation). Historical and comparative methods are the main methods used in the research paper. The author finds out that researchers of all periods dedicated their scientific works to the problem of legal, social and economic status of Ukrainian women. Some works deal with the female entrepreneurship that is a new phenomenon in Ukraine’s economy. A considerable number of publications describe the history of the women’s liberation movement in Ukraine and its peculiarities. The women’s participation in political life of Ukraine is discussed from different viewpoints. Gender studies appeared in the mid-1990s. In the author’s opinion, the problem of public and political participation of Ukrainian women is not completely investigated and requires further comprehensive research.
The problem of the women’s public and political activity in Ukrainian science
Keywords: жіноча проблематика; громадсько-політична активність жінок; жіночі студії; гендерні дослідження; women’s problems; women’s public and political activity; women’s workshops; gender studies